1979
DOI: 10.2172/5600572
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical determinants of the efficiency of photogalvanic conversion of solar energy

Abstract: A photogalvanic cell is a battery in which the cell solution absorbs light directly to generate species which, upon back reaction through an external circuit with the aid of suitable electrodes, produces electric power; photoactivation of the electrodes is 'not involved. The charge-carrying species have storage capacity if they are long-lived and can be prevented from engaging in degradativc back reactions in bulk solution. The efficiency of a photogalvanic cell for the conversion of photon energy into electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…11 The solar conversion efficiency 0.06% is reported for primitive beaker photogalvanic cell design (two chambered design). 61 Later on, cell design was changed by Shigehara et al to a glass chamber having two compartments (Pt electrode used in each compartment) separated by a spacer for which potential 190 mV and current 2.7 μA is reported. 48 Kamat et al observed potential 170 mV for homogeneous photogalvanic cell designed with three electrodes that is, two working (anode and cathode) and one reference saturated calomel electrode.…”
Section: Comparison Of the Present Cylindrical Cell Design With The Conventional Cell Designsmentioning
confidence: 99%
“…11 The solar conversion efficiency 0.06% is reported for primitive beaker photogalvanic cell design (two chambered design). 61 Later on, cell design was changed by Shigehara et al to a glass chamber having two compartments (Pt electrode used in each compartment) separated by a spacer for which potential 190 mV and current 2.7 μA is reported. 48 Kamat et al observed potential 170 mV for homogeneous photogalvanic cell designed with three electrodes that is, two working (anode and cathode) and one reference saturated calomel electrode.…”
Section: Comparison Of the Present Cylindrical Cell Design With The Conventional Cell Designsmentioning
confidence: 99%
“…Fill factor (n) = V pp i pp /V oc i sc (6) Conversion efficiency = V pp × i pp /10.4(mW/cm 2 ) × 100 per cent (7) where V pp , i pp , V oc , and i sc are the potential at power point, current at power point, open circuit voltage, and the short circuit current. The system at its optimum condition is exposed to sunlight.…”
Section: Current Potential (I-v ) Characteristics Of the Cellmentioning
confidence: 99%
“…From the literature survey [2][3][4][5][6][7][8][9] of photogalvanic cells with different dyes, it is observed that photochemical solar energy conversion and storage depend on structures, reduction potential, and absorption maxima of dyes used in the cells. To utilize the broad solar spectrum, mixed dyes instead of a single dye may be used in solar cell [10,11].…”
Section: Introductionmentioning
confidence: 99%